ADAPTIVE TEXTILE PRODUCTS: JOINTS AND THEIR FEATURES - ОСТАПЕНКО, Н. В.; КОЛОСНІЧЕНКО, О. В.; ОЧЕРЕТНА, Л. В.; ТОКАР, Г. М.; ТОКАР, Г. М.; РУБАНКА, А. І.; МАМЧЕНКО, Я. О. (Art and Design, 2022)
Purpose. The aim of the article is to explore existing types of adaptive clothing for people with different needs, to summarize information on the types of sewing accessories for the manufacture of adaptive garments for various purposes. Methodology. Information-research and visual-analytical approaches are used in combination with general scientific methods of typological systematization and comparative analysis of existing types of sewing accessories for the foreign and domestic production of adaptive clothing. Results. The article investigates the range of existing adaptive garments for various purposes, lists their main functions, identifies the compositional, design and technological features. The range of modern sewing accessories is analyzed and the list of leading world and domestic manufacturers is presented. The most common types of accessories for the manufacture of adaptive clothing using the principles of transformation for consumers are identified and systematized, the materials used for their manufacture are described. The design features of the types of sewing accessories are revealed, their functional possibilities and characteristic features are analyzed. Scientific novelty. Varieties of sewing accessories for adaptive clothing by purpose, area and method of connection are structured, their types are characterized and characteristic structural and compositional features of shape, size, material, etc. are revealed. The practical significance of the obtained results is to identify the main types of adaptive clothing for different purposes and determine their main functions. The types of means of connection used for the production of adaptive clothing by the principles of transformation are summarized and graphically presented. The information base of sewing accessories for various functional purposes, materials for their production, methods of connection and locations has been developed. The results can be used in the further development of clothing for this purpose.